A gender-natural resources tango: Water, land, and forest research - Joshi, Deepa; Monterroso, Iliana; Gallant, Bryce; Perera, Kokila; Peveri, Valentina (International Food Policy Research Institute, 2021)
Gender relations shape identities, norms, rules, and responsibilities for women and men, and mediate access to, use, and management of water resources, as well as ownership, tenure, and user rights to land and forests (and related infrastructure, services, technologies innovations and interventions). Natural resource management (NRM) interventions thus have important implications for women’s labor, time, decision-making, and transformational gains.